Analisis Pengaruh Kompetensi, Motivasi Dan Disiplin Kerja Terhadap Kinerja Pegawai: Badan Perencanaan Pembangunan Daerah Provinsi Papua - Buiney, Meilan; Kambuaya, Balthasar; Risamasu, Ferdinand (Magister Manajemen Universitas Cenderawasih, 2024)
This study aims to analyze the influence of competence, work motivation, and work discipline on employee performance at the Regional Development Planning Agency of Papua Province. The research employed a survey method with a quantitative approach, where data were collected through questionnaires distributed to all employees as respondents in this study. Data analysis was conducted using multiple linear regression with the assistance of IBM SPSS 24 statistical software. The results indicate that: (1) competence has a positive and significant effect on employee performance, supporting the first hypothesis; (2) work motivation has a positive but not significant effect on employee performance, supporting the second hypothesis; (3) work discipline has a positive and significant effect on employee performance, supporting the third hypothesis; and (4) competence, work motivation, and work discipline collectively influence employee performance. These findings emphasize that competence and work discipline are key factors in improving employee performance. Meanwhile, although work motivation tends to have a positive effect, it is not significant in the context of this study. The implications of this research can serve as a foundation for policy-making to enhance employee effectiveness and productivity, particularly through competence development and the implementation of optimal work discipline.